Dampak Aktivitas Bertanya Peserta Didik Terhadap Hasil Belajar - Andriani, Windi; Supriadi, Supriadi; Junaidi, Junaidi; Alimir, Alimir (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
This research is motivated by several problems that the authors found in Class VII Pondok Arabi Darul Yamani As-Syarif, especially in the Akidah Akhlak subject. Where in learning there are still students who are classified as active in asking questions, but their learning outcomes are mediocre and there are still students who are classified as passive in their beta, but their grades are very good. This research is a correlational quantitative research. The sampling technique used is total sampling, namely the population size is the same as the sample of 50 students. From the results of the analysis and discussion, it is obtained from the results of hypothesis testing using simple linear regression, then the results of parametric statistical tests then Ho is rejected and H1 is accepted. While the personalcorrelation value was 0.763, which means that it shows a positive relationship that the more active students ask questions, the higher the learning outcomes of Akidah Akhlak. So that it can be concluded that there is a relationship / correlation between the activeness of askingquestions and the learning outcomes of the Aqidah Akhlak in class VII at Pondok Arabi Darul Yamani As-Syarif Kec. Sasak Pasaman Coastal Realm.